Supplementation of polyunsaturated fatty acids (PUFAs) and aerobic exercise improve functioning, morphology, and redox balance in prostate obese rats - Veras, Allice Santos Cruz [UNESP]; Gomes, Rayana Loch; Almeida Tavares, Maria Eduarda [UNESP]; Giometti, Inês Cristina; Cardoso, Ana Paula Mattoso Miskulin [UNESP]; da Costa Aguiar Alves, Beatriz; Lenquiste, Sabrina Alves; Vanderlei, Luiz Carlos Marques [UNESP]; Teixeira, Giovana Rampazzo [UNESP] (My University, 2021)
The high-fat diet (HFD) stimulates an increase in lipids and can be prejudicial for harmful to prostatic morphogenesis. Polyunsaturated fatty acid (PUFAs) have anti-inflammatory and antioxidant action in some types of cancer. The combination of aerobic physical exercise and PUFA can be more effective and reduce the risk of death. The study evaluates the effects of aerobic physical exercise associated with omega-3 (fish and chia oils), on the ventral prostate of Wistar rats those fed with HFD. Here, we report that HFD modified the final body weight and the weight gain, decreased the expression of the androgen receptor and increased prostatic inflammation via TNF-α produced damage prostatic like intraepithelial neoplasia. The supplementation with fish oil decreases final body weight, reduced BCL-2 and inflammation compared to chia oil; aerobic physical exercise associated with fish oil reduced lipids circulant and prostatic, increased proteins pro-apoptotic expression and reduced IL-6 (p < 0.0001) and TNF-α potentiating the CAT (p = 0.03) and SOD-1 (p = 0.001) expression. Additionally, the chia oil increased the NRF-2 (p < 0.0001) and GSS (p = 0.4) genes. PUFAs reduced the damage caused by excessive high-fat diet in the prostate so that there is greater effectiveness in omega-3 intake, it is necessary to associate with aerobic physical exercise.